Koordinasi Penanganan Bencana Letusan Gunung Merapi Tahun 2010 Di Kabupaten Sleman - Paramita, Asiska Bunga; ., Yuwanto; Martini, Rina (Journal of Politic and Government Studies, 2013)
The eruption of Mount Merapi in 2010 in Distric of Sleman has resulted in many victims who died due to heat clouds and cold lava flood. Lack of prevention (mitigation) in minimizing the impact of a disaster gives poor disaster management in District of Sleman. Slowness in handling the victim becomes one of the results of the lack of coordination in the field, coordination which should be run by unstructured organization ​​SATLAK PB in disaster prevention and handling is not running smoothly. This is caused by lack of understanding of the chairman and members of the SATLAK PB towards disaster management cycle, so that efforts to handling the victims in the first week after disaster are in chaos. Those occurrences made ​​the victims and refugees become neglected, victims and refugees who are supposed to get all their rights such as shelter, health care and assistance are totally not obtained. According those descriptions, then it is conducted a research in order to determine the issues occurred in the efforts to handling disaster victims especially in the implementation of coordination and also to determine factors that are influencing the coordination. In this research, the type of research used is description research to describe, explain and analyze the data from the result of coordination happened. This research is aimed to assess the process of coordination between institutions and actors in the handling and mitigation of disaster. Based on the analysis of the data obtained that the disaster handling, particularly in disaster handling in the district of Sleman, especially in coordination goes not so well. One of the causes of slowness in the evacuation of the victims and provision of relief at the beginning of disaster is lack of coordination in the field. Lack of coordination due to the absence of leaders of SATLAK PB making parties or other actors take over the tasks of SATLAK PB. The alteration are strongly felt since the military and other actors involved in the handling of the disaster victims, but communication which is established does not go so well, especially in the distribution of relief. Where parties who want to provide relief to victims immediately are not allowed giving directly regarding the procedure. From the analysis, it is time SATLAK PB should fix both of the structures, personnel, and leadership which is prohibited to be done by a bureaucrat. This is to avoid overlapping of work and for the efficiency goals of the organization which are as coordinator of disaster management and in the field